2017
DOI: 10.5606/tftrd.2017.23169
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory arthritis complicated by inflammatory bowel disease: two case reports

Abstract: Case 1-A 49-year-old male diagnosed with psoriasis two and a half years earlier was admitted to our hospital with complaints of tenderness and swelling in the first and second metacarpophalangeal (MCP) joints of the right hand and psoriatic skin lesions on the extensor side of the right forearm (Figure 1).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Considering ours and the previously reported overlapping cases of UC and RA, we found that these criteria were applicable in all 13 cases (4 men and 9 women) (Table 2) (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). Seropositive RA preceded UC in all patients, and the median duration between the onset of the two diseases was six years.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Considering ours and the previously reported overlapping cases of UC and RA, we found that these criteria were applicable in all 13 cases (4 men and 9 women) (Table 2) (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). Seropositive RA preceded UC in all patients, and the median duration between the onset of the two diseases was six years.…”
Section: Discussionmentioning
confidence: 59%
“…Typical EIMs include scleritis, erythema nodosum, pyoderma gangrenosum, arthritis of the extremities, ankylosing spondylitis, sclerosing cholangitis, and biliary tract diseases. However, to our knowledge, there are only 12 published cases with overlap of chronic RA and UC (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…Colitis influences the distal piece of the colon and makes non-transmural irritation, huge rot and ulceration in the layers of mucosa and submucosa (Randhawa et al, 2014). These sicknesses are characterized clinically through provocative confusion in gastrointestinal lot went with looseness of the bowels, torments in midsection, weight decrease, nausea and obsessive changes like a deficiency of mucosal dysfunctions, aggravation and cell invasion (Cengiz et al, 2017). Acceptance of colitis may be because of the openness to various incendiary specialists and because of creation of free extremists (Hanauer, 2006;Saad et al, 2019).…”
Section: Introductionmentioning
confidence: 99%